Multisectoral community development in Nepal had greater effects on child growth and diet than nutrition education alone. - Miller, Laurie; Neupane, Sumanta; Joshi, Neena; Lohani, Mahendra; Rogers, Beatrice; Neupane, Shailes; Ghosh, Shibani; Webb, Patrick. (Tufts University. Tisch Library., 2019)
Objective: To compare the impact on child diet and growth of a multisectoral community intervention v. nutrition education and livestock management training alone.; Keywords: Multisectoral community intervention, Child growth, Child diet, Animal-source foods, Nepal, Nutrition education, Women's groups.; Feed the Future Innovation Lab for Nutrition, USAID Contract No. AID-OAA-L-10-000006, managed by Tufts University's Gerald J. & Dorothy R. Friedman School of Nutrition Science and Policy